Macrophages—bone marrow mesenchymal stem cells crosstalk in bone healing - Fan, Siyu; Sun, Xin; Su, Chuanchao; Xue, Yiwen; Song, Xiao; Deng, Runzhi (Frontiers in Cell and Developmental Biology, 2023)
Bone healing is associated with many orthopedic conditions, including fractures and osteonecrosis, arthritis, metabolic bone disease, tumors and periprosthetic particle-associated osteolysis. How to effectively promote bone healing has become a keen topic for researchers. The role of macrophages and bone marrow mesenchymal stem cells (BMSCs) in bone healing has gradually come to light with the development of the concept of osteoimmunity. Their interaction regulates the balance between inflammation and regeneration, and when the inflammatory response is over-excited, attenuated, or disturbed, it results in the failure of bone healing. Therefore, an in-depth understanding of the function of macrophages and BMSCs in bone regeneration and the relationship between the two could provide new directions to promote bone healing. This paper reviews the role of macrophages and BMSCs in bone healing and the mechanism and significance of their interaction. Several new therapeutic ideas for regulating the inflammatory response in bone healing by targeting macrophages and BMSCs crosstalk are also discussed.